2013
DOI: 10.1136/bjophthalmol-2012-302123
|View full text |Cite
|
Sign up to set email alerts
|

Combined therapy of cyclosporine A and mycophenolate mofetil for the treatment of birdshot retinochoroidopathy: a 12-month follow-up

Abstract: These results suggest that combined IMT with CSA and MM for BSRC is well tolerated and associated with long-term control of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 27 publications
(19 reference statements)
1
36
0
1
Order By: Relevance
“…With regards to functional assessment, it is well known that in BSCR, exclusive BCVA assessment should not be considered as a reliable parameter for evaluating therapy response 7 20 23 24. In the present study, BCVA, visual field and full-field ERG parameters remained stable during the treatment and no worsening of the retinal function was observed.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…With regards to functional assessment, it is well known that in BSCR, exclusive BCVA assessment should not be considered as a reliable parameter for evaluating therapy response 7 20 23 24. In the present study, BCVA, visual field and full-field ERG parameters remained stable during the treatment and no worsening of the retinal function was observed.…”
Section: Discussionsupporting
confidence: 50%
“…However, the outcome of MMF treatment was not analysed separately from the other immunosuppressive drugs. Recently, Cervantes-Castaneda et al 20 presented their results of combined immunosuppressive therapy with cyclosporine A and MMF in patients with BSCR. The authors reported on the control of inflammation in 67.4% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome for treated eyes was better than untreated eyes but the inflammation returned on the discontinuation of therapy. A subsequent report from the same group used combination therapy with mycophenolate mofetil and CSA in an attempt to reduce the possibility of CSA-associated nephrotoxicity 26. There was effective control of inflammation (based on vitritis and angiographic leakage), but a 55% incidence of significant side effects, systemic hypertension being the most common.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that aggressive and sustained treatment is probably needed in the majority of patients; [41,42] not more than 10-15 % of patients present a relatively mild course [8]. Once the diagnosis is established, our criterion to treat is the occurrence of visual field defects.…”
Section: Therapy and Evolutionmentioning
confidence: 98%